Pelatihan Tata Cara dan Etika Melamar Kerja Dalam Bahasa Inggris Bagi Siswa SMAN 1 Batulayar Kabupaten Lombok Barat - Tri Setianingsih; Siti Syafi’atul Qomariyah; Bq. Zuhrotun Nafisah; Terasne Terasne (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2021)
The purpose of community service activities is to increase insight into ethics and procedures for applying for jobs in English which will be needed for students at SMAN 1 Batulayar in particular, to enter the world of work after graduating from school. During the pre-test before the implementation of the service activities, it was found that almost 90% of the 20 grade 3 students at SMAN 1 Batulayar did not know the ethics and procedures for applying for jobs in English. So it can be said that this activity is very useful for students. The method used in this service is the diffusion of knowledge and the practice of implementing ethics and procedures for applying for jobs in English. The result of this service activity is that the third grade students participating in this activity become more enthusiastic and more confident in learning conversation and vocabulary related to job interviews in English. Moreover, our team also provides a pocket book in the form of summaries of several interviews and how to write a job application letter in English which they can learn whenever they want. This can be seen from the post test results after this service activity was carried out, namely an increase from 20 students who did not understand everything, almost 90%, namely 18 students understood ethics and procedures for applying for jobs in English.